Entangled Geographies, Contested Narratives: The Canning Marbles and the Ottoman Response to Antiquity - Özkaya, Belgi̇n Turan (Muqarnas, 2022)
The history of archaeology in the nineteenth century has conventionally been studied from the point of view of Europeans, who are credited as the inventors of modern archaeology. Although the blatantly Eurocentric perspective of earlier scholarship has been challenged in recent decades by a proliferation of works on the “source countries” where the bulk of archaeological material originated before being displaced to Europe, the trajectory of European archaeology has not been abandoned as the measure by which to assess emerging sensibilities about antiquity in the nineteenth century. In this essay, I trace the origins of a group of “marbles” from the British Museum, the Canning marbles, and propose to rethink a mid-nineteenth-century Ottoman attempt to establish a museum to house such “marbles” in the light of the Ottoman exhibitionary practices in the longue durée. My aim is to challenge both contemporaneous European narratives on nineteenth-century Ottoman attitudes to antiquity and current scholarship on Ottoman museology that attributes its proper emergence to the last two decades of the century, after the well-known Ottoman polymath Osman Hamdi Bey resumed the directorship of the Müze-i Hümāyūn (Ottoman Imperial Museum).